PELAYANAN PENGURUSAN SURAT IZIN MENGEMUDI (SIM) DI KANTOR SATLANTAS POLRES KAMPAR - Berian Hariadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to determine the service of making a driver's license (SIM) at the Kampar Police Satlantas Office and to analyze the inhibiting factors. The focus of the research which includes SIM service standards, namely service procedures, completion time, service costs, service products, facilities and infrastructure, competence of service providers and inhibiting factors at the Kampar Police Satlantas Office in SIM management services. The data sources in this study are divided into two The form of data is key informants and other informants and secondary data whose data sources are obtained from reading sources such as organizational structure, goals and functions, vision and mission of the Kampar Police. In this study using data collection techniques by conducting library research and field research through observation, interviews and documentation. The analytical tool used is the type of descriptive research with qualitative methods. The results of the research that has been carried out, that the Kampar Police Satlantas Office has not been able to satisfy the SIM applicants in terms of the services provided. Through research conducted with the process of observation, interviews and documentation, there are still obstacles in terms of service in the SIM management process. Most of these things are caused by the service time which is very far from the predetermined SOP.Keywords: Service, Driver's License.